2022
DOI: 10.3389/fendo.2022.975209
|View full text |Cite
|
Sign up to set email alerts
|

Obesity paradox and aging: Visceral Adiposity Index and all-cause mortality in older individuals: A prospective cohort study

Abstract: BackgroundThe relationship between body mass index (BMI) and mortality in older adults diminished. It is necessary to examine other factors that may accurately predict mortality in older adults. The visceral adiposity index (VAI) is an uncomplicated marker specific to the gender that incorporates anthropometric data and lipid profiles. VAI has been proposed as a marker of visceral adipose tissue dysfunction and of the related cardiometabolic risk. The aim of this study was to evaluate the link of VAI with all-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 32 publications
1
7
1
Order By: Relevance
“…A large‐scale nationwide study from the UK reported that VAI was significantly correlated with an increased risk of all‐cause mortality 49 . Although this finding is consistent with our study, a J‐shaped link correlation was observed in a sample of elderly Americans with a mean age of 73.4 years 50 . Nevertheless, the latter could not be confidently compared with our results due to the significant difference in age and the different nature of accompanying diseases among older and younger populations, which could have affected the mortality rate.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…A large‐scale nationwide study from the UK reported that VAI was significantly correlated with an increased risk of all‐cause mortality 49 . Although this finding is consistent with our study, a J‐shaped link correlation was observed in a sample of elderly Americans with a mean age of 73.4 years 50 . Nevertheless, the latter could not be confidently compared with our results due to the significant difference in age and the different nature of accompanying diseases among older and younger populations, which could have affected the mortality rate.…”
Section: Discussionsupporting
confidence: 91%
“…49 Although this finding is consistent with our study, a J-shaped link correlation was observed in a sample of elderly Americans with a mean age of 73.4 years. 50 Nevertheless, the latter could not be confidently compared with our results due to the significant differ- Furthermore, we did not find any significant difference between LAP and VAI for CVD incidence, CVD mortality, or all-cause mortality. Analysis comparing the predictive performance of VAI and LAP with BMI indicated greater AUC for VAI and LAP according to the incidence of CVD; however, considering all-cause mortality, BMI had significantly greater AUC.…”
Section: Discussioncontrasting
confidence: 59%
“…First, we found different associations between CVAI and CVD and cancer mortality. Mounting evidence indicates that visceral adipose tissue (VAT), as measured by machines or calculated by predictive models, is strongly associated with risk of mortality in different populations 18–28 . However, this remains controversial, and little is known about the relationship between visceral fat and mortality in the Chinese population.…”
Section: Discussionmentioning
confidence: 99%
“…Mounting evidence indicates that visceral adipose tissue (VAT), as measured by machines or calculated by predictive models, is strongly associated with risk of mortality in different populations. [18][19][20][21][22][23][24][25][26][27][28] However, this remains controversial, and little is known about the relationship between visceral fat and mortality in the Chinese population. Some studies have reported that the presence of greater VAT increases the risk of CVD mortality, 19,27 which was consistent with our findings.…”
Section: Discussionmentioning
confidence: 99%
“…A possible explanation might consist in a better nutrition in general meaning a better immune response against chronic infections or other threatening complications, which are often a cause of death in the lower BMI dialysis population (13). This is also supported by the J-shaped association of dialysis mortality, where the nadir of the curve corresponds to normal BMI patients (14), while the historical unintended weight loss is an independent predictor of death (15).…”
Section: Introductionmentioning
confidence: 91%